2003
DOI: 10.1002/art.11094
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and angiogenesis in osteoarthritis

Abstract: Objective. To quantify the relationship between inflammation and angiogenesis in synovial tissue from patients with osteoarthritis (OA).Methods. Hematoxylin and eosin staining and histologic grading for inflammation were performed for 104 patients who met the American College of Rheumatology criteria for OA and had undergone total joint replacement or arthroscopy. A purposive sample of synovial specimens obtained from 70 patients was used for further analysis. Vascular endothelium, endothelial cell (EC) prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
258
1
11

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(292 citation statements)
references
References 24 publications
14
258
1
11
Order By: Relevance
“…8,18 Angiogenesis and inflammation in synovial tissue are highly associated with osteoarthritis. 4,19 Synovium is important for maintaining the health of joints. During disease progression, infiltrated macrophages within the synovial membrane produce angiogenic factors, such as vascular endothelial growth factor (VEGF), cytokines, and lowmolecular weight factors, and they impair homeostasis of the articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,18 Angiogenesis and inflammation in synovial tissue are highly associated with osteoarthritis. 4,19 Synovium is important for maintaining the health of joints. During disease progression, infiltrated macrophages within the synovial membrane produce angiogenic factors, such as vascular endothelial growth factor (VEGF), cytokines, and lowmolecular weight factors, and they impair homeostasis of the articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…3 Furthermore, vascular growth is also higher in the synovium from patients with than without osteoarthritis and is associated with synovitis. 4 Osteochondral angiogenesis facilitates the progression of osteoarthritis. 5 Angiogenesis and inflammation interact and mutually affect each other in the osteoarthritic joint.…”
mentioning
confidence: 99%
“…Synovial angiogenesis is also a feature of chronic synovitis in both humans and animals (30,47,48). In the present study, we demonstrated increased EC proliferation during chronic synovitis 29 days after coinjection of carrageenan and FGF-2.…”
Section: Discussionmentioning
confidence: 99%
“…40 VEGF is expressed by macrophages and known to induce endothelial cell chemotaxis and mediating vascular permeability, an important process in inflammation. [77][78][79] Interestingly, intra-articular injection of VEGF in mice has increased calcification of AC, cartilage degradation, and subchondral bone sclerosis, implicating a role of VEGF in OA. 80 ICAM-1 is upregulated by osteoarthritic synoviocytes in response to pro-inflammatory stimuli and plays an important role in transendothelial migration of T cells and may therefore mediate the migration and infiltration of lymphocytes in the synovium.…”
Section: Infiltrating Cd3mentioning
confidence: 99%